Australian politics and Antarctic sovereignty: themes, protagonists and antagonists - Hodgson-Johnston, I (Australian Journal of Maritime & Ocean Affairs, 2015)
Australia's claim to the Australian Antarctic Territory (AAT) is not widely recognised internationally. Discussing enforcement of Australian domestic law in the Southern Ocean, defending the territorial claim and other emotive issues related to Antarctica therefore requires some domestic sensitivity to broader international diplomacy. Using qualitative and quantitative analysis methods to identify the political parties who most often raise issues of Antarctica, the major themes of Antarctic policy and politics since 1998, and the discussions of Antarctic sovereignty by political parties. Through this analysis, the different approaches of the Australian Labor Party, the Federal Liberal-National Party Coalition and the Australian Greens to Antarctic sovereignty-related issues are identified and discussed. While broadly there is tripartisan support for Antarctic policies, some differences between political parties do exist.